Research collaboration outputs between the European Union and Africa: the case of co-authored scientific articles between Finland and Africa - Jauhiainen Jussi S. (Geographical Society of Finland, 2025)
I analyzed co-authored international peer-reviewed scientific articles that resulted from research collaborations between scholars in the European Union (EU) and African countries, with a particular focus on the case of Finland. Among the 28 EU member states, Finland ranked 13th in terms of the quantity of co-authored scientific articles produced through these collaborations. I found that from 2015 to 2021, scholars from universities, research institutes, and other organizations in African countries and Finland co-authored more than 4,700 international peer-reviewed articles. Despite the doubling of co-authored Finland–Africa peer-reviewed scientific articles in international journals annually during this period, these articles accounted for less than one percent of all international peer-reviewed scientific articles in Africa, and their proportional share decreased over time. The most common fields of collaboration were medical sciences and natural science. Of Finland–Africa articles, almost 1,500 focused on Africa. The University of Helsinki and South African universities were the most active collaborators. Given these findings, it is crucial to address the implementation of the European Commission’s strategy for partnerships with Africa and Finland’s collaboration strategies with Africa to encourage more inclusive research collaboration among scholars from Finland, Europe, and Africa.